2020
DOI: 10.1109/access.2020.3018861
|View full text |Cite
|
Sign up to set email alerts
|

Backhaul-Aware Optimization of UAV Base Station Location and Bandwidth Allocation for Profit Maximization

Abstract: Unmanned Aerial Vehicle Base Stations (UAV-BSs) are envisioned to be an integral component of the next generation Wireless Communications Networks (WCNs) with a potential to create opportunities for enhancing the capacity of the network by dynamically moving the supply towards the demand while facilitating the services that cannot be provided via other means efficiently. A significant drawback of the state-of-the-art have been designing a WCN in which the service-oriented performance measures (e.g., throughput… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…In [14], the achievable rate of the UAV-based mmWave wireless backhaul link is investigated and then, the authors analyzed the minimum cache hit probability to achieve a certain backhaul rate requirement. The UAV-BS location and bandwidth allocation problems is studied in [15] to maximize the throughput without exceeding the backhaul and access capacities. A novel spectrum management architecture for UAV-assisted mmWave networks is suggested in [16] to overcome the problem related to the spatio-temporal distribution of the wireless network traffic.…”
Section: B Literature Review and Motivationmentioning
confidence: 99%
“…In [14], the achievable rate of the UAV-based mmWave wireless backhaul link is investigated and then, the authors analyzed the minimum cache hit probability to achieve a certain backhaul rate requirement. The UAV-BS location and bandwidth allocation problems is studied in [15] to maximize the throughput without exceeding the backhaul and access capacities. A novel spectrum management architecture for UAV-assisted mmWave networks is suggested in [16] to overcome the problem related to the spatio-temporal distribution of the wireless network traffic.…”
Section: B Literature Review and Motivationmentioning
confidence: 99%
“…Simulation results showed that the proposed method can achieve robust performance under the impact of users' mobility. By defining a piecewise-linear function of gained transmission rate that captures the profit of mobile users, the authors in (Cicek et al, 2020) addressed the joint UAV-BS position and bandwidth allocation optimization problem. In order to maximize the total network profit, they proposed a heuristic algorithm to solve the formulated mixed-integer nonlinear programming problem.…”
Section: Unmanned Aerial Vehicle-assisted Iab Networkmentioning
confidence: 99%
“…The authors also found the optimal 3D location of a UAV-BS to maximize the number of users whose Signal-to-Noise Ratio (SNR) requirement is met. In [14], the authors addressed the problem of finding the 3D location of one UAV and the bandwidth allocation for each user to maximize the profitability of the provided service. Since the problem was modeled as a Mixed Integer Non-Linear Programming problem, to overcome the complexity, a search algorithm was proposed.…”
Section: Introductionmentioning
confidence: 99%